Tunable elastic modulus in Mn-based antiferromagnetic shape memory alloys. (25th July 2016) - Cui, S S; Shi, S; Zhao, Z M; Cui, Y G; Liu, C; Yuan, F; Hou, J W; Wan, J F; Zhang, J H; Rong, Y H
Abstract: Compared with the normal relation between temperature ( T ) and elastic modulus ( E ) in most materials, martensitic transformation (MT) and magnetic transition could result in the softening of elastic modulus (d E/ d T > 0) within a narrow range of T (<100 °C). It becomes possible in MnFeCu alloys to tune this range and broaden it to about 200 °C through combining MT and paramagnetic-antiferromagnetic (P-A) transition. The alloying elements and their contents play a key role in making MT separate from P-A transition, in which first-order MT made a greater contribution to this maximum value than second-order P-A transition. The intrinsic mechanism is that MT can continue causing the modulus to soften even after the P-A transition ends. This wide range keeps stable under different cooling/heating rates. An expression for d E/ d T is deduced based on the proposed free energy model and the corresponding theoretical curve (d E/ d T-T ) gives a reasonable explanation on the experimental results in MnFeCu alloys. A modulus–temperature–composition phase diagram is obtained to describe such critical behaviors and it is found that there exists a specific triangle zone in which d E/ d T > 0. The present results may enrich approaches to designing new functional materials, e.g. the elastic and Elinvar alloys.